Real-Time Data Transformation in Connected Vehicles: A Systematic Analysis of Architectures, Methods, and Applications - Anush kumar Thati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The emerging landscape of connected vehicles has introduced unprecedented challenges in processing and utilizing vast streams of real-time data. This article presents a comprehensive framework for real-time data transformation in connected vehicle environments, addressing the critical aspects of data processing architectures, analytical methodologies, and practical implementations. The article examines the integration of edge computing, cloud-based solutions, and hybrid architectures to optimize data transformation workflows while minimizing latency and bandwidth constraints. The article analyzes various data types generated by connected vehicles, including telemetry, diagnostics, and user-generated content, and explores their transformation requirements for enabling advanced functionalities such as predictive maintenance, traffic optimization, and enhanced driver assistance systems. Through multiple industry case studies, the article demonstrates the practical application of proposed frameworks and their impact on operational efficiency, safety metrics, and overall vehicle performance. Our findings highlight the significance of balanced architectural choices, the role of machine learning in data transformation processes, and the importance of addressing security and scalability challenges. This article contributes to the growing body of knowledge in connected vehicle technologies while providing practical insights for automotive industry practitioners implementing real-time data transformation solutions.